2008
DOI: 10.1002/bit.22071
|View full text |Cite
|
Sign up to set email alerts
|

Advanced monitoring of high‐rate anaerobic reactors through quantitative image analysis of granular sludge and multivariate statistical analysis

Abstract: Four organic loading disturbances were performed in lab-scale EGSB reactors fed with ethanol. In load disturbance 1 (LD1) and 2 (LD2), the organic loading rate (OLR) was increased between 5 and 18.5 kg COD m(-3) day(-1), through the influent ethanol concentration increase, and the hydraulic retention time decrease from 7.8 to 2.5 h, respectively. Load disturbances 3 (LD3) and 4 (LD4) were applied by increasing the OLR to 50 kg COD m(-3) day(-1) during 3 days and 16 days, respectively. The granular sludge morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 26 publications
(26 reference statements)
2
13
0
Order By: Relevance
“…13 The application of organic residues, in which compositions per batch are highly fluctuating, 14 or, in general, a changing feedstock can cause considerable process instabilities. Any disturbance occurs in the reaction phase at first, i.e., in the microbial cell.…”
Section: ■ Discussionmentioning
confidence: 99%
“…13 The application of organic residues, in which compositions per batch are highly fluctuating, 14 or, in general, a changing feedstock can cause considerable process instabilities. Any disturbance occurs in the reaction phase at first, i.e., in the microbial cell.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Since the biogas production and methane content decreased, while acetate concentration increased, and the ethanol concentration remained undetected in the effluent, is clear that the methanogenesis was inhibited. It is possible to speculate that the Methanosaeta genera, which is a very slow growing archaea could have been selectively washed out, as already observed during organic loading disturbances [21].…”
Section: Reactor Performancementioning
confidence: 97%
“…According to Costa et al (2007Costa et al ( , 2009a, the optimal dilution factor is between 1:5 and 1:10 for anaerobic granular sludge samples with volatile solids around 30 g L −1 . Regarding aerobic activated sludge (Mesquita et al 2010b), an optimum 1:5 dilution factor was found for samples with total suspended solids (TSS) ranging from 2.3 to 4.7 mg L −1 .…”
Section: Amaral 2003mentioning
confidence: 99%
“…Four organic loading disturbances were performed in labscale EGSB reactors fed with ethanol (Costa et al 2009a). Granule erosion/fragmentation was observed after increase the organic loading rate (OLR) from 5 to 18.5 kg COD m −3 day −1 , given the decrease from 90 to 70 % of the percentage of aggregate projected area with D eq >1 mm.…”
Section: Organic Overloadsmentioning
confidence: 99%